TOWS analysis for sustainable ecotourism development and state support during the pandemic: The Aral Sea region of Uzbekistan - Saidmamatov, Olimjon; Matyakubov, Umidjon; Khodjaniyazov, Elbek; Day, Jonathon; Ibadullaev, Ergash; Chuponov, Sanat; Bekjanov, Dilmurad; Matniyozov, Murodjon; Matyusupov, Bunyod (Turyzm/Tourism, 2021)
Evaluating the current ecotourism situation in the Aral Sea region of Uzbekistan and offering strategies for its sustainable development are the main objectives of the study. The threats, opportunities, weaknesses and strengths (TOWS) analysis was applied to identify the required management strategies. The article aims to review the literature on ecotourism promotion in the Aral Sea region. Based on TOWS, the results show that state support during the pandemic should be strategically coordinated to secure the sustainability of the ecotourism industry in Uzbekistan.